Performance analysis of paper, BER and snr of OFDM for different modulation techniques: a survey - Y.K, Shobha; H.G, Rangaraju (International Journal of Engineering and Technology, 2018)
The subcarriers must be kept orthogonal to each other, which are called as an Orthogonal Frequency Division Multiplexing to achieve a better performance by using multi carrier modulation. But an injury to reputation of an OFDM method is of its enormous Peak power ratio. This paper is purely based on performance analysis of PAPR, BER and SNR by using different modulation techniques and different schemesÂ Â